2021
DOI: 10.26499/ijea.v3i2.74
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Make Students Confused and Anxious: a Comparisons Between Australia, Indonesia, and Singapore in The 2015 Timss

Abstract: The main purpose of this study is to find out  the perceptions about Mathematics that confuse and anxious 2015 TIMSS participants in Australia, Indonesia, and Singapre. The data in this study is the 2015 TIMSS data that has been released to the public and has available  for development purpose research. The research method used is quantitative method. The population of this study is students' perceptions of Mathematics subject that confuse and worry students aged 15 years in three countries who are studying in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Based on the analysis of students' difficulties according to the PISA level 1 indicator, there are still some students who are wrong in arithmetic operations. Students often miscalculate in answering math questions, this is because they believe when answering the questions can make them confused and afraid (Safari, 2021). Mathematical arithmetic operations are one of the important components that students should master because the next material will be interconnected (Safriani et al, 2019).…”
Section: Analysis Of Question Numbermentioning
confidence: 99%
“…Based on the analysis of students' difficulties according to the PISA level 1 indicator, there are still some students who are wrong in arithmetic operations. Students often miscalculate in answering math questions, this is because they believe when answering the questions can make them confused and afraid (Safari, 2021). Mathematical arithmetic operations are one of the important components that students should master because the next material will be interconnected (Safriani et al, 2019).…”
Section: Analysis Of Question Numbermentioning
confidence: 99%
“…This can be proven from several times the results of the Trends in International Mathematics and Science Study (TIMSS) with highlevel cognitive questions that measure critical thinking skills. In the 2015 TIMSS, Indonesia was ranked 46th out of 51 countries with a score of 397 (Safari, 2021). Then in the 2018 Program for International Student Assessment (PISA) results, it shows that Indonesia's achievement in mathematics has a score of 379 which indicates a decrease of 7 points from that obtained in 2015 (Setiawan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of poor mathematical understanding and ability can also be seen from Indonesia, which was ranked 46 th out of 51 countries with a score of 397 in the Trends in International Mathematics and Science Study (TIMSS) 2015 Results in Mathematics, which assessed mathematics and science knowledge of students around the world with high-level cognitive questions that measure mathematical understanding and ability (Safari, 2021). In addition, the 2018 Program for International Student Assessment (PISA) result showed that Indonesia scored 379 in mathematics, which was a 7-point decrease from the previous score (Setiawan et al, 2021).…”
mentioning
confidence: 99%